2018
DOI: 10.2147/cia.s169223
|View full text |Cite
|
Sign up to set email alerts
|

<em>Lactobacillus helveticus</em> (ATCC 27558) upregulates <em>Runx2</em> and <em>Bmp2</em> and modulates bone mineral density in ovariectomy-induced bone loss rats

Abstract: PurposeOsteoporosis is one of the major health concerns among the elderly population, especially in postmenopausal women. Many menopausal women over 50 years of age lose their bone density and suffer bone fractures. In addition, many mortality and morbidity cases among the elderly are related to hip fracture. This study aims to investigate the effect of Lactobacillus helveticus (L. helveticus) on bone health status among ovariectomized (OVX) bone loss-induced rats.MethodsThe rats were either OVX or sham OVX (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…The other studies used senescence-accelerated mouse (SAMP) [ 60 , 61 ], virgin fisher rat [ 62 ], and ND4 Swiss Webster retired breeder mice [ 63 ]. Out of 37 studies, 17 publications were performed on male [ 29 , 33 , 35 , 38 , 41 , 45 , 46 , 48 , 49 , 52 55 , 60 , 61 , 63 , 64 ], 17 on female [ 30 , 32 , 34 , 36 , 37 , 39 , 40 , 42 , 44 , 50 , 51 , 56 , 57 , 59 , 62 , 65 ], and 3 on both gender [ 28 , 31 , 43 ]. In fourteen investigations, female rats had ovariectomy surgery that induced osteoporosis [ 36 , 37 , 39 , 40 , 42 , 44 , 47 , 51 , 56 , 57 , 59 , 62 , 66 ], and in two studies, diabetic rats were included [ 38 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other studies used senescence-accelerated mouse (SAMP) [ 60 , 61 ], virgin fisher rat [ 62 ], and ND4 Swiss Webster retired breeder mice [ 63 ]. Out of 37 studies, 17 publications were performed on male [ 29 , 33 , 35 , 38 , 41 , 45 , 46 , 48 , 49 , 52 55 , 60 , 61 , 63 , 64 ], 17 on female [ 30 , 32 , 34 , 36 , 37 , 39 , 40 , 42 , 44 , 50 , 51 , 56 , 57 , 59 , 62 , 65 ], and 3 on both gender [ 28 , 31 , 43 ]. In fourteen investigations, female rats had ovariectomy surgery that induced osteoporosis [ 36 , 37 , 39 , 40 , 42 , 44 , 47 , 51 , 56 , 57 , 59 , 62 , 66 ], and in two studies, diabetic rats were included [ 38 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Out of 37 studies, 17 publications were performed on male [ 29 , 33 , 35 , 38 , 41 , 45 , 46 , 48 , 49 , 52 55 , 60 , 61 , 63 , 64 ], 17 on female [ 30 , 32 , 34 , 36 , 37 , 39 , 40 , 42 , 44 , 50 , 51 , 56 , 57 , 59 , 62 , 65 ], and 3 on both gender [ 28 , 31 , 43 ]. In fourteen investigations, female rats had ovariectomy surgery that induced osteoporosis [ 36 , 37 , 39 , 40 , 42 , 44 , 47 , 51 , 56 , 57 , 59 , 62 , 66 ], and in two studies, diabetic rats were included [ 38 , 45 ]. Animals were fed by L. reuteri [ 30 , 31 , 40 , 43 , 45 , 46 , 56 , 57 , 64 ], L. casei [ 34 , 38 40 , 51 , 63 ], L. paracasei [ 42 , 44 , 54 , 65 …”
Section: Resultsmentioning
confidence: 99%
“…BMP2 is a growth factor that plays a crucial role in bone development and osteoblastic differentiation by activating signalling molecules such as Smad 1/5/8 and regulating osteogenic genes like RUNX2 (Parvaneh et al . 2018). RUNX2 is a major gene that regulates the expression of osteoblastic genes and is a critical transcription factor for osteoblast differentiation (Gilbert et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the expression of RUNX2, which was unaffected after ovariectomy, was upregulated upon treatment with the two Lactobacillus-FMPs, which provided the evidence that L. plantarum A41 and L. fermentum SRK414-FMPs could regulate BMP2 signalling. BMP2 is a growth factor that plays a crucial role in bone development and osteoblastic differentiation by activating signalling molecules such as Smad 1/5/8 and regulating osteogenic genes like RUNX2 (Parvaneh et al 2018). RUNX2 is a major gene that regulates the expression of osteoblastic genes and is a critical transcription factor for osteoblast differentiation (Gilbert et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that there are certain probiotic strains that are capable of blocking the decreased bone‐breaking force and of normalising the decreased trabecular bone parameters induced by ovariectomy. Parvaneh and colleagues reported that L. helveticus increases the BV/TV, BMD and the bone‐breaking force in OVX rats (Parvaneh et al 2018) via upregulating expression of bone morphogenetic protein‐2 ( BMP‐2 ) pathway‐related genes. Also, Dar and co‐workers also reported that L. acidophilus exhibits anti‐osteoporotic effects on osteoporotic mice by increasing BMD and bone parameter values such as Tb.Th and BV/TV (%) through balancing immune‐related regulatory T cells (Treg) and helper T cells (Th) (Dar et al 2018).…”
Section: Resultsmentioning
confidence: 99%